(untitled) (Khairulummah, 2022)
Abstract After the advent of Islam and the revelation of the Qur’an, in order to simplify and understand the knowledge, meanings and demands of the Qur’an, the famous Companions, Taabi’een, and jurists started working on Islamic sciences according to their own knowledge and ability, from which many people benefited. And it is happening till today and this chain will continue till the Day of Resurrection. My topic is QUROON-E-ULA KAI TAFSEERI MAKATEB-E-FIKAR. The objective of this topic is that, it tells us about QUROON-E-ULA KAI TAFSEERI MAKATEB-E-FIKAR and in which era this process came into being. Many books published before in this topic but at this point of time it is consider to be an article. When I started to work and explore on this article. I have learnt many things and I enjoyed al lot to work on this article because it became a motive for my heart’s peace.